Еволюція концепції публічно-приватного партнерства у 1980-2020-х роках - Petrova, Iryna P. (Institute of Industrial Economics of NAS of Ukraine, 2023)
The evolution of changes in the concept of public-private partnership is very relevant in today's world. The growth of global problems, such as financial crises, climate change, social imbalances and economic transformations, creates a need for new strategies and concepts of cooperation between different sectors of society. Public-private partnerships are a key mechanism to address these challenges, as they provide mechanisms for cooperation between public and private actors to achieve common goals.The purpose of the study is to substantiate the evolutionary changes of the concept of public-private partnership.Using bibliographic analysis and visualization of data from the Web of Science based on VOSviewer, ten research clusters were identified and analyzed, which reflect various topics and their interrelationships, contributing to the systematization of changes in the concept of public-private partnerships. Phases of the evolutionary transformation of the public-private partnership concept: Public-Private Partnership 1.0. Traditional Public-Private Partnership; Public-Private Partnership 2.0. People-first Public-Private Partnership; Public-Private Partnership 3.0. Climate-smart Public-Private Partnership; Public-Private Partnership 4.0. Sustainable public-private partnership for post-war reconstruction.It was determined that in the use of public-private partnership in industry, a change in the role of this sphere is observed. In the «Traditional Public-Private Partnership» industry has a key role in infrastructure construction, providing materials and advanced technologies for infrastructure projects; «People-first Public-Private Partnership» - ensuring quality medical care and improving the health care system; «Climate-smart public-private partnership» - reducing the impact of climate change on production through investments in environmentally friendly technologies and ensuring sustainability of food supplies; «Sustainable public-private partnership for post-war reconstruction» - post-war reconstruction, providing the necessary materials and resources for the construction and reconstruction of infrastructure. Also, during the COVID-19 pandemic, industry, particularly pharmaceuticals, is working with government and other sectors to develop new treatments and vaccines. These joint efforts help overcome crises and improve living conditions in affected areas.It was revealed that the concept of public-private partnership is insufficiently developed in Ukraine. «Traditional public-private partnership», despite 20 years of implementation, did not receive active implementation of infrastructure projects. «People-first Public-Private Partnership» is just beginning its development. It is noted that the «Sustainable public-private partnership for post-war reconstruction» is updated for post-war conditions, as it contributes to attracting international resources for economic and social recovery, but requires a systematic approach and adaptation to the specifics of the Ukrainian situation. The implementation of PPP in Ukraine requires systematic recommendations and consideration of international experience for effective use in the restoration and reconstruction of infrastructure and strategic objects.